Partial substitution of phosphorus fertilizer with iron-modified biochar improves root morphology and yield of peanut under film mulching - Luo, Xiulan; Wang, Dewei; Liu, Yuting; Qiu, Yuanze; Zheng, Junlin; Xia, Guimin; Elbeltagi, Ahmed; Chi, Daocai (Frontiers in Plant Science, 2024)
Peanut production is being increasingly threatened by water stress with the context of global climate change. Film mulching have been reported to alleviate the adverse impact of drought on peanut. Lower phosphorus use efficiency is another key factor limiting peanut yield. Application of iron-modified and phosphorus-loaded biochar (BIP) has been validated to enhance phosphorus utilization efficiency in crops. However, whether combined effect of film mulching and BIP could increase water use efficiency and enhance peanut production through regulating soil properties and root morphologies needs further investigation. Therefore, a two-year pot experiment using a split-plot design was conducted to investigate the effects of phosphorus fertilizer substitution using BIP on soil properties, root morphology, pod yield, and water use of peanut under film mulching. The main plots were two mulching methods, including no mulching (M0) and film mulching (M1). The subplots were four combined applications of phosphorus fertilizer with BIP, including conventional phosphorus fertilizer rates (PCR) without BIP, P1C0; 3/4 PCR with 7.5 t ha-1 BIP, P2C1; 3/4 PCR with 15 t ha-1 BIP, P2C2; 2/3 PCR with 7.5 t ha-1 BIP, P3C1; 2/3 PCR with 15 t ha-1 BIP, P3C2. The results indicated that regardless of biochar amendments, compared with M0, M1 increased soil organic matter and root morphology of peanut at different growth stages in both years, increased peanut yield and water use efficiency (WUE) by 18.8% and 51.6%, respectively, but decreased water consumption by 25.0% (two-year average). Irrespective of film mulching, P2C1 increased length, surface area, and volume of peanut root at seedling by 16.7%, 17.7%, and 18.6%, at flowering by 6.6%, 19.9%, and 29.5%, at pod setting by 22.9%, 33.8%, and 37.3%, and at pod filling by 48.3%, 9.5%, and 38.2%, respectively (two-year average), increased soil pH and organic matter content during peanut growing season, and increased soil CEC at harvest. In general, the M1P2C1 treatment obtained the optimal root morphology, soil chemical properties, WUE, and increased peanut yield by 33.2% compared to M0P1C0. In conclusion, M1P2C1 treatment effectively improved soil chemical properties, enhanced root morphology of peanut, and ultimately increased peanut yield and WUE.